LOW COST AND COMPACT DIRECTIONAL COUPLER FOR ULTRAWIDEBAND APPLICATIONS - Dyg Norkhairunnisa, Abang Zaidel; Sharul Kamal, Abdul Rahim; Norhudah, Seman; Tharek A., Rahman; A., Abdulrahman (Wiley Periodicals, Inc., 2012)
A design of a compact size (35 15 mm2 ) 3-dB coupler with ultrawideband (UWB) characteristic is demonstrated in this article. The proposed design is accomplished by forming two diamond-shaped microstrip lines that are broadside coupled by a slot at the middle ground plane. The dimension of the design was initialized using a simple mathematical formula and optimized using the CST microwave studio simulator. The design coupler is fabricated and measured. It shows comparable results of the simulation and measurement for the phase difference between two output ports, return loss, isolation, and 3-dB coupling over an UWB frequency range between 4 and 8.34 GHz. VC 2012 Wiley Periodicals, Inc. Microwave Opt Technol Lett 54:670–674, 2012; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.26616.